Synthesis and Characterization of 1-Amino-2-Naphthol Hydrochloride and Dyeing Potentials of 1-(1-Phenylazo)-2-Naphthol - I. C, Onunkwo; C. M, Ejikeme; G. A, Osuji (International Journal of Chemistry and Materials Research, 2020)
Emergence of diverse classes of dyes occurred due to constant effort to find specific dye or class of dyes of industrial importance for various applications. Azo dyes have been reported to possess diverse applications and properties. In the present study, 1-(1-Phenylazo)-2-naphthol azo dye was synthesized by diazotization of aniline and azo coupling with 2-naphthol. This was further reduced with stannous chloride under reflux to produce 1-amino-2-naphthol hydrochloride. The results obtained from the UV-vis and IR spectra were used to elucidate the structural characteristics of the reduced compound. The dyeing potentials of the 1-(1-Phenylazo)-2-naphthol with material fabrics showed that the compound was reasonably fast to washing, rubbing and light with application of ingrain azoic dyeing method.